Prospects for detecting signs of life on exoplanets in the JWST era - Sara Seager; Luis Welbanks; Lucas Ellerbroek; William Bains; Janusz J. Petkowski (Proceedings of the National Academy of Sciences, 2025)
The search for signs of life in the Universe has entered a new phase with the advent of the James Webb Space Telescope (JWST). Detecting biosignature gases via exoplanet atmosphere transmission spectroscopy is in principle within JWST’s reach. We reflect on JWST’s early results in the context of the potential search for biological activity on exoplanets. The results confront us with a complex reality. Established inverse methods to interpret observed spectra—already known to be highly averaged representations of intricate three dimensional (3D) atmospheric processes—can lead to disparate interpretations even with JWST’s quality of data. Characterizing rocky or sub-Neptune-size exoplanets with JWST is an intricate task, and moves us away from the notion of finding a definitive “silver bullet” biosignature gas. Indeed, JWST results necessitate us to allow “parallel interpretations” that will perhaps not be resolved until the next generation of observatories. Nonetheless, with a handful of habitable-zone planet atmospheres accessible given the anticipated noise floor, JWST may continue to contribute to this journey by designating a planet as biosignature gas candidate. To do this we will need to sufficiently refine our inverse methods and physical models for confidently quantifying specific gas abundances and constraining the atmosphere context. Looking ahead, future telescopes and innovative observational strategies will be essential for the reliable detection of biosignature gases.